2013
DOI: 10.1039/c3cc43511c
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 supported Pd@Ag as highly selective catalysts for hydrogenation of acetylene in excess ethylene

Abstract: ZnO-Al 2 O 3 derived from layered double hydroxides (ZnAl-LDH) was successfully applied for dispersion of Pd-Ag bimetallic catalysts for the selective hydrogenation of acetylene to ethylene and the Pd-Ag/ZnO-Al 2 O 3 catalyst showed the best catalytic performance among the prepared samples. It was found that the catalyst carrier of ZnO-Al 2 O 3 metal-oxides derived form ZnAl-LDH could significantly suppress the over-hydrogenation of acetylene to obtain the relatively higher selectivity of ethylene. The introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…The selectivities at >99.5% conversion, which is a greater challenge and more relevant to the industrial process, were also compared. Although the selectivity toward ethene decreases sharply for both catalysts at such a high conversion, the value over PdAg MCs/HT (70%) is slightly higher than that over PdAg NPs/HT [74,75,78], but the values are lower than those for PdCu catalysts reported by Anderson and co-workers [6]. As for the intrinsic activity, the PdAg MCs/HT catalyst has a TOF of 0.045 s À1 , which is higher than the values for monometallic Pd NPs/HT and PdAg NPs/HT catalysts (Entries 1 and 2).…”
Section: Partial Hydrogenation Of Acetylenementioning
confidence: 85%
“…The selectivities at >99.5% conversion, which is a greater challenge and more relevant to the industrial process, were also compared. Although the selectivity toward ethene decreases sharply for both catalysts at such a high conversion, the value over PdAg MCs/HT (70%) is slightly higher than that over PdAg NPs/HT [74,75,78], but the values are lower than those for PdCu catalysts reported by Anderson and co-workers [6]. As for the intrinsic activity, the PdAg MCs/HT catalyst has a TOF of 0.045 s À1 , which is higher than the values for monometallic Pd NPs/HT and PdAg NPs/HT catalysts (Entries 1 and 2).…”
Section: Partial Hydrogenation Of Acetylenementioning
confidence: 85%
“…[299][300][301] Nanomaterial-catalyzed hydrogenations of alkynes, alkenes, aromatic nitro compounds and ketones have received much interest in the last decade because of their use in the synthesis of important raw materials along with the remarkable effectiveness of nanomaterials in catalyzing such reactions. [308][309][310][311] 4.1.1. Among such processes, catalytic transfer hydrogenation (CTH) reaction is becoming increasing popular because of its wide usage and versatility.…”
Section: Hydrogenation Reactionsmentioning
confidence: 99%
“…A number of recent studies have looked at the choice of second metal as well as the method of introduction. Han et al [51] reported a novel method for introduction of Ag to Pd/TiO 2 catalysts via sequential photo-deposition. Based on FTIR of adsorbed CO it was thought that this resulted in the preferential deposition of Ag onto a Pd core, as opposed to metal mixing.…”
Section: Addition Of a Second Metalmentioning
confidence: 99%